Pengembangan Nilai-Nilai Islam Dalam Kajian Ilmu Ekonomi - Muhammad Akhyar Adnan (Millah: Journal of Religious Studies, 2002)
This article attempts to develop the Islamic value in the economic science. As for the writer, there are many contradictions in Muslim life. Normatively, Islam has the ideal teaching of life; but on contrary there is no any correlation between the ideal doctrine and Muslim practice life. The contradictions seem when there is no any balance between vertical side of a Muslim (hablum minallah) and horizontal life among a Muslim with his society (hablum minannas). According to the writer, to solve this problem may be started from preparing a good belief (aqidah), and it will help in solving other life side such as worship (ibadah), social affairs (muamalah), and good attitude (akhlakul karimah). Furthermore, to develop the Islamic value in all aspects must through two kinds both statements (qauUyyah/ quran or prophet traditions) and nature (qauniyyah/Allah's creation). The first is the source of value and the latter is the field of research and approach. Both are in practice will complement each other. If it is connected with the economic science, the work way may be like this: all statements in al quran or prophet tradition may be the source of economic science, but in its practice does not mean ignore the real economic system.